The Effect of Using Context-Based Physics Learning Videos on Critical Thinking Skills of XI Grade High School Students - Rezza Septia Sari; Desnita Desnita (Universitas Lambung Mangkurat, 2023)
Education in the 21st century demands the readiness of students to face the ever-evolving era. This study aims to determine the effect of using context-based physics learning videos on the critical thinking skills of class XI students at SMA N 1, Suliki District. Students' critical thinking skills at SMA N 1 Suliki District are still low because the use of instructional media has not honed students' critical thinking skills. One solution to this is through the use of context-based physics learning videos. This type of research is quasi-experimental. Posttest-Only Control Design research design. The population in this study were all students from class XI SMA N 1 Suliki District for the 2021/2022 academic year. The process of taking samples is carried out through a purposive sampling technique, namely choosing two classes with the same average. The data collected is from students' critical thinking skills, including